2016
DOI: 10.1093/jme/tjw213
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Diversity of Tick-Borne Pathogens in NymphalIxodes scapularis(Acari: Ixodidae) in Eastern National Parks

Abstract: Tick-borne pathogens transmitted by Ixodes scapularis Say (Acari: Ixodidae), also known as the deer tick or blacklegged tick, are increasing in incidence and geographic distribution in the United States. We examined the risk of tick-borne disease exposure in 9 national parks across six Northeastern and Mid-Atlantic States and the District of Columbia in 2014 and 2015. To assess the recreational risk to park visitors, we sampled for ticks along frequently used trails and calculated the density of I. scapularis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 55 publications
3
30
0
1
Order By: Relevance
“…Pathogen testing varied by laboratory and over time; groups of ticks were tested by different laboratories for different pathogens. Testing of Ixodes and Dermacentor ticks followed each laboratory's protocols (33,(41)(42)(43)…”
Section: Dna Extraction and Molecular Identificationmentioning
confidence: 99%
“…Pathogen testing varied by laboratory and over time; groups of ticks were tested by different laboratories for different pathogens. Testing of Ixodes and Dermacentor ticks followed each laboratory's protocols (33,(41)(42)(43)…”
Section: Dna Extraction and Molecular Identificationmentioning
confidence: 99%
“…For example, rickettsial diseases are steadily increasing within the Americas [11] and further, recent studies have shown that the most predominant human biting tick, Amblyomma americanum , is capable of acquiring, maintaining, and transmitting Rickettsia rickettsii [12]. The steady increase in tick populations and pathogens [13], increased vector competency of human biting ticks for rickettsial diseases[12], and the movement toward an epidemic of tick-transmitted pathogens [14,15] highlights the significance of research aimed to identify novel mechanisms of control to curb the health and economic burden of ticks.…”
Section: Introductionmentioning
confidence: 99%
“…El principal vector es la ninfa de la garrapata de patas negras, Ixodes scapularis 23 . Su tamaño es tan pequeño, que muchas veces los pacientes no notan la mordedura, por lo que se debe educar a los visitantes de zonas endémicas sobre la importancia de las acciones preventivas como el uso de repelentes y ropa adecuada para así minimizar la exposición a garrapatas 24 . La distribución geográfica de esta enfermedad se limita al hemisferio norte.…”
Section: Caso Clínicounclassified